Clinical utility of the pan-immune-inflammation value in breast cancer patients - Qi, Xiaoyan; Qiao, Boyang; Song, Tingting; Huang, Dan; Zhang, Hui; Liu, Yang; Jin, Qi; Yang, Ming; Liu, Delong (Frontiers in Oncology, 2023)
The newly discovered pan-immune-inflammation value (PIV) has been illustrated to have good prognostic value for cancer patient prognosis. However, the prognostic usefulness of PIV in breast cancer patients is unknown. As a result, to aid the clinic in providing a distinctive and trustworthy biomarker to better assess breast cancer patient's prognosis, we conducted this meta-analysis to investigate the relationship between PIV and the survival of breast cancer patients. Methods: We conducted a systematic search of Pubmed, Embase, the Cochrane Library, and the CNKI databases to screen for eligible studies published up to April 2023. Outcomes included overall survival (OS), progression-free survival (PFS), and pathological complete response (pCR). The hazard ratio (HR) and the corresponding 95% confidence interval (CI) were used as the indicators. STATA 15.0 software was used to perform meta-analysis, sensitivity analysis, and publication bias analysis. Results: A total of eight articles, involving 2953 patients, met the inclusion criteria and were included in this meta-analysis. The results showed that patients with higher PIV levels had a significantly shorter OS (HR: 2.045, 95% CI: 1.355-3.086, P = 0.001) and PFS (HR: 1.466, 95% CI: 1.163-1.848, P = 0.001). Besides, the PIV value was negatively correlated with the efficacy of neoadjuvant chemotherapy. Sensitivity analysis showed that the results of this study were reliable and stable. Conclusions: PIV has a good prognostic value in breast cancer patients and is expected to be a prognostic biomarker for breast cancer.